Challenges and strategies for the organization of the health sector in the face of the COVID-19 pandemic (Research, Society and Development, 2020)
The health sector in Brazil is going through an extremely critical moment due to the confrontation of the COVID-19 pandemic. Within the scope of the Health Unic System, reactive management actions have been taken on an emergency basis to respond to this complex biological disaster. In this sense, the objective was to analyze the challenges and potential strategies aimed at the emergency organization of the health sector to better respond to the COVID-19 pandemic, in the national context. This is an exploratory study, developed using the document analysis method, whose sources of evidence were technical-scientific documents related to public health emergency and disaster risk management actions, which were treated by thematic content analysis category. The results show that, in general, the challenges faced by managers refer to the need to adopt fast and resolute actions. To this end, four strategic measures were identified: 1) organization of health situation rooms; 2) interaction of agents and sectors for health response to the pandemic; 3) structuring of emergency plans; and 4) development of specific assistance models. It was concluded that the understanding and undertaking of these measures, from the point of view of risk management of emergencies and disasters in public health, are urgent, since the non-observance of such measures can produce serious damages to human health, especially for more socially vulnerable communities and groups. The highlighted measures may be useful to municipal and state managers in the face of the COVID-19 pandemic, and to other possible future situations of emergencies and biological disasters.